A hybrid nuclear model approach for neutral-current inelastic neutrino-nucleus scattering - Papoulias, Dimitrios K.; Hellgren, Matti; Suhonen, Jouni (HNPS Advances in Nuclear Physics, 2026)
We present nuclear structure calculations for neutral-current inelastic neutrino-nucleus scattering off the stable 203/205Tl isotopes using a novel hybrid approach combining the nuclear shell-model (NSM) and the microscopic quasiparticle-phonon model (MQPM). The hybrid model leverages the accuracy of NSM for low-lying states and the computational efficiency of MQPM for higher-energy excitations. We compute scattering cross sections as functions of incoming neutrino energy and nuclear recoil energy, and present event rates for various neutrino sources, including solar neutrinos, stopped-pion neutrinos, and diffuse supernova neutrino background. The results demonstrate the importance of inelastic channels, particularly at higher neutrino energies where they become competitive with coherent elastic neutrino-nucleus scattering.